1977
DOI: 10.1073/pnas.74.7.2865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antitubulins on the redistribution of crosslinked receptors on the surface of fibroblasts and epithelial cells

Abstract: Substrate-attached normal mouse fibroblasts, transformed mouse fibroblasts (L strain), and epithelial cells (MPTR strain) were incubated with two ligands crosslinking different groups of the surface receptors: concanavalin A and cationic ferritin. Surface-attached ligands were revealed by an indirect immunofluorescence method. Incubation of control cells with these ligands induced the patching of corresponding surface receptors and the clearing of these receptors from the surface zones located on thelamelar cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…From the finding that actin accumulates in lymphocytes in the same regions as receptor caps (Gabbiani et al, 1977;Oliver et al, 1977;Toh and Hard, 1977) it has been claimed that receptor patches are actively collected into a cap through their association with membrane-linked actin filaments which participate in an actinmyosin sliding filament mechanism (Edelman, 1976;Nicolson and Poste, 1976;Bourguignon and Singer, 1977;Vasiliev and Gelfand, 1977). While the presently available data points to an involvement of actin in receptor movement there exists so far no conclusive evidence for the direct association of membrane receptors with subcortical actin filaments.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…From the finding that actin accumulates in lymphocytes in the same regions as receptor caps (Gabbiani et al, 1977;Oliver et al, 1977;Toh and Hard, 1977) it has been claimed that receptor patches are actively collected into a cap through their association with membrane-linked actin filaments which participate in an actinmyosin sliding filament mechanism (Edelman, 1976;Nicolson and Poste, 1976;Bourguignon and Singer, 1977;Vasiliev and Gelfand, 1977). While the presently available data points to an involvement of actin in receptor movement there exists so far no conclusive evidence for the direct association of membrane receptors with subcortical actin filaments.…”
Section: Discussionmentioning
confidence: 92%
“…Earlier studies have indicated loss of Con A receptors from the leading edge regions of fibroblasts and epithelial cells both under normal conditions (Abercrombie et al, 1972;Vasiliev et al, 1976) and in the presence of drugs which disrupt microtubules (Domnina et al, 1977). But a correlation between this phenomenon and the ultrastructure and extent of the underlying cortical filament web was not made.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the results for epithelial cells show conflicting data. Whereas the polarized morphology of some epithelial cells is disrupted by the addition of such MT-specific drugs [Domnina et al, 1985 al., 19851, other reports have found that there is no dependence upon an intact MT network for the maintenance of a polarized morphology [Di Pasquale, 1975;Downie, 1975;Domnina et al, 1977;Chernoff and Overton, 1979;Euteneuer and Schliwa, 1984;Middleton et al, 19881. Recently, Middleton et al [ 19891 described that drug-induced depolymerization blocked the polarized movements of 2" but not 1" chick heart fibroblasts. 2" CHFs are derived from 1" CHFs as a result of either culture over 48 h or passaging but have rather different characteristics.…”
Section: Introductionmentioning
confidence: 99%